2009
DOI: 10.1149/1.3229969
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Ion Effects in the Corrosion Kinetics of Intermetallics in Acidic Solutions

Abstract: The electrodissolution rates of polycrystalline Sb and InSb in Cl --free acid perchlorate and acid chloride solutions have been investigated. The rest potentials of Sb and InSb in these solutions were linear functions of pH and chloride ions. Furthermore, Tafel behavior was observed for both Sb and InSb in these solutions and electrodissolution rates increased with increase in pH and Cl -. Reaction orders of the electrodissolution rates with respect to pH (or H + ) and Cl -were determined. Solution analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…4,14 It has been shown that the perchlorate (ClO 4 − ) anions tend to complex less with the surface metal atoms as compared to chloride anions (Cl − ). 15 As a result perchlorate ions are less corrosive than chloride anions but still cause localized pitting corrosion on magnesium alloys (in a similar fashion to Cl − ions). 14 The chosen electrolyte for this investigation is 0.1M sodium perchlorate (NaClO 4 ) as to allow sufficient conductivity, reduce the corrosion rates, prevent tip blockage, and allow longer time periods for investigation.…”
Section: Resultsmentioning
confidence: 99%
“…4,14 It has been shown that the perchlorate (ClO 4 − ) anions tend to complex less with the surface metal atoms as compared to chloride anions (Cl − ). 15 As a result perchlorate ions are less corrosive than chloride anions but still cause localized pitting corrosion on magnesium alloys (in a similar fashion to Cl − ions). 14 The chosen electrolyte for this investigation is 0.1M sodium perchlorate (NaClO 4 ) as to allow sufficient conductivity, reduce the corrosion rates, prevent tip blockage, and allow longer time periods for investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Its corrosion in chloride-containing environments has been studied even less. Such studies have been carried out to investigate antimony as a part of intermetallic compounds [29], galvanic coupled to carbon steel [30] as well as in connection with the development of binary intermetallic compounds and antifriction composite materials [31].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study [2,4] showed that, when alloyed potentiostatically, the uppermost surface of the resultant Cu-Sn phase depends on the potential during the alloying: The main phase obtained at +5 mV vs. Sn 2+ /Sn 0 is Cu 6 Sn 5 intermetallic compound, while that at +20 mV is Cu 3 Sn. In other words, this process will be a convenient tool to compare various surface properties of these two intermetallic phases.…”
mentioning
confidence: 99%
“…The electrochemical deposition of alloys and compounds is a fundamental technology for thin-layer processing in the fields of, for example, surface finishing and electronic materials. Recently, we have demonstrated that Cu-Sn alloy layers with composition of 40-60 wt.% Sn can be formed by an electrochemical reductiondiffusion (RD) method using galvanic contact [1][2][3] or potentiostatic [2,4] technique. The target Cu-Sn alloy called "speculum metal" appears silver-gray and has been investigated as a promising hypoallergenic coating to replace Ni underlayer for Cr or Au electroplating.…”
mentioning
confidence: 99%
See 1 more Smart Citation